MET activation confers resistance to cetuximab, and prevents HER2 and HER3 upregulation in head and neck cancer. Issue 3 (11th February 2019) - Novoplansky, Ofra; Fury, Matthew; Prasad, Manu; Yegodayev, Ksenia; Zorea, Jonathan; Cohen, Limor; Pelossof, Raphael; Cohen, Liz; Katabi, Nora; Cecchi, Fabiola; Joshua, Ben‐Zion; Popovtzer, Aron; et al.
Abstract : An understanding of the mechanisms underlying acquired resistance to cetuximab is urgently needed to improve cetuximab efficacy in patients with head and neck squamous cell carcinoma (HNSCC). Here, we present a clinical observation that MET pathway activation constitutes the mechanism of acquired resistance to cetuximab in a patient with HNSCC. Specifically, RNA sequencing and mass spectrometry analysis of cetuximab‐sensitive (Cetux Sen ) and cetuximab‐resistant (Cetux Res ) tumors indicated MET amplification and overexpression in the Cetux Res tumor compared to the Cetux Sen lesion. Stimulation of MET in HNSCC cell lines was sufficient to reactivate the MAPK pathway and to confer resistance to cetuximab in vitro and in vivo . In addition to the direct role of MET in reactivation of the MAPK pathway, MET stimulation abrogates the well‐known cetuximab‐induced compensatory feedback loop of HER2/HER3 expression. Mechanistically, we showed that the overexpression of HER2 and HER3 following cetuximab treatment is mediated by the ETS homologous transcription factor (EHF), and is suppressed by MET/MAPK pathway activation. Collectively, our findings indicate that evaluation of MET and HER2/HER3 in response to cetuximab in HNSCC patients can provide the rationale of successive line of treatment. Abstract : What's new? Resistance to cetuximab is a major obstacle in the treatment of patients with head and neck squamous cell carcinoma (HNSCC), though the underlying mechanisms of resistance remain unclear. In the present study, analyses of tumor samples from an HNSCC patient with exceptional clinical response to cetuximab monotherapy implicate MET pathway activation as a causative factor in acquired cetuximab resistance. Experiments in vitro and in vivo show that MET confers resistance to cetuximab via activation of the MAPK pathway. MET stimulation further limits cetuximab‐induced HER2/HER3 overexpression, highlighting the importance of HER2/HER3 and MET evaluation when monitoring patient reponse to cetuximab.